Proteinograma sérico de bezerros recém-nascidos da raça Holandesa obtido por eletroforese em gel de poliacrilamida - Fagliari, J.J. [UNESP] (2006)
The serum protein concentration of newborn Holstein calves determined by means of sodium dodecyl sulphate-polyacrylamide (SDS-PAGE) was studied. Blood samples from 40 healthy newborn calves were obtained 48 hours after birth. Calves had been given 3 liters of colostrum within 2 hours after birth, following by dose corresponding by 15% of animal weight each 24 hours. The results showed three different proteinograms: 19 calves had 14 proteins with molecular weights (MW) ranging from 28,000 D to 170,000D (proteinogram 1); 11 calves had 14 proteins with MW ranging from 18,000 to 170,000 D (proteinogram 1); and 10 calves had 12 proteins with MW ranging from 28,000 D to 170,000 D (proteinogram 3). The three groups presented similar IgG levels. The highest serum concentration of ceruloplasmin were verified in proteinogram 3, which had the lowest serum level of protein with MW 58,000D. It was verified a1-antitrypsin only in proteinogram 2, which had no proteins with MW of 42,000 D and 37,000D. The highest serum concentrations of IgA and protein with MW 58,000 D, and the lowest serum levels of transferrin, haptoglobin, and acid glycoprotein were verified in proteinogram 3. Measurement of serum protein concentrations by SDS-PAGE may be useful in monitoring the occurrence of hypogammaglobulinemia and the neonatal disease in calves.